Folic Acid Supplement Prevents Phenytoin-Induced Gingival Hyperplasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the Division of Pediatric Neurology, Neurosciences Centre, New Delhi, India, performed a randomized, double-blind, placebo-controlled 6-month trial of oral folic acid supplement (0.5 mg/day) in children aged 6-15 years treated with phenytoin for epilepsy.